The Level of Health Literacy and Affecting Factors in Type 2 Diabetes Mellitus Patients - Gizem Özcan; Ayşe Özkaraman (Dokuz Eylul University, 2021)
Background: Health literacy is the search for people to find information about their health, learn and guide their lives in line with this information. Type 2 diabetes mellitus (T2DM), which is one of the chronic diseases needs to take responsibility as well as health care professionals in the follow-up, treatment and care process. In this case, the concept of health literacy comes to the fore. Objectives: This study was planned to determine the level of health literacy in T2DM patients and to examine the factors affecting the level of health literacy. Methods: The cross-sectional and descriptive type study was carried out between 05.12.2018-21.06.2019, its sample was 18 years old and above, conscious, T2DM patient for at least one year and 700 patients volunteering to participate in the study. Data were collect edusing the Individual Literature Form and the Health Literacy Questionnaire-European Union (HLS-EU- Q47) Scale. Results: The average age of the patients participating in the study is 61.80 ± 10.49 years, 75.4% are women, 74.3% are married and 71.4% are primary school graduates. T2DM diagnosis period of 34.4% is 16 years or more. HLS-EU-Q47 general health index health literacy average score is sufficient with 35.76 ± 7.20. There is a significant negative relationship between age and health literacy, those who have higher education, married, more than their expenses, do not have any other chronic diseases accompanying T2DM, patients who receive education about T2DM from healthcare workers or other sources have a higher level of health literacy. It was determined to be high (p <.05). Conclusion: It is important in this research that health literacy in the T2DM of various socio-demographic and medical factors is important.